EFEKTIVITAS MODEL PEMBELAJARAN GENIUS LEARNING DENGAN BANTUAN MEDIA POWER POINT TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH MATEMATIKA SISWA PADA MATERI SEGITIGA KELAS VII SMP SWASTA FREE METHODIST 2 MEDAN T.P 2019/2020 - Siahaan, Rohani Seplin (Jurnal Visi Eksakta, 2025)
This research includes quasi-experimental research. The experimental research method can be interpreted as a research method used to find the effect of certain treatments on others under controlled conditions (Sugiyono, 2016: 72). This study aims to see whether the Genius Learning model is effective with the help of Power Point media on concept understanding and problem solving skills. The research design uses the one-shot case study. This study involved one experimental class that was given one-time treatment with the Genius Learning model. The population of this study were all VII grade students of SMP Swasta Free Methodist 2 Medan T.P 2019/2020 consisting of 3 classes. The variables in this study consisted of two types, namely independent (independent variable (X)) and dependent (dependent variable (Y)) variables. From the observation data above, the average score of the teacher's ability to teach is 4.167, so by comparing with the average score of the teacher's ability to teach above, it can be concluded that the teacher's ability to teach in this study is in the good category.